DNA Repair Activity of Ilex paraguariensis in Human Cells In Vitro - Erben, Melina (2014)
Yerba mate (Ilex paraguariensis) has been consumed as popular infusions in South America for centuries, with potential beneficial effects on health. The aim of this study was to evaluate yerba mate antioxidant properties in human leucocytes exposed in vitro to oxidative damage, using the Comet assay. Human cells were exposed to 10 μM H2O2 and then allowed to repair with increasing concentrations of two different yerba mate infusions: 10 μl/mL, 100 μl/mL and 1000 μl/mL. Damage Index (DI) and the percentage of damage reduction (%DR) were calculated. DI showed that both infusions produced similar protective effects (p > 0.05) and the %DR indicated a decreased in oxidative damage as infusion concentration increases (p < 0.05). The greatest protective effects were found using the highest concentration of mate (1000 μl/mL). Thus, we conclude that the regular ingestion of Ilex paraguariensis infusions could contribute to antioxidant defense on humans.